2017
DOI: 10.1111/ans.14258
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three fixation methods in treatment of tibial fracture in adolescents

Abstract: All three treatments had satisfactory outcomes, and EF was correlated with the highest rate of complications in our series of adolescents treated with a tibial fracture. However, we cannot currently recommend that all fractures might be suitable for ESINF. The choice of fixation will remain influenced by surgeon preference in term of expertise and experience, patient and fracture characteristics, and patients and family preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Five studies [17,23,24,28,30] reported the length of hospital stay for both study cohorts. All the studies found the patients in the circular external fixation cohort had shorter hospital stays than those in the ORIF cohort (Fig 4).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Five studies [17,23,24,28,30] reported the length of hospital stay for both study cohorts. All the studies found the patients in the circular external fixation cohort had shorter hospital stays than those in the ORIF cohort (Fig 4).…”
Section: Plos Onementioning
confidence: 99%
“…Five studies [17,18,26,29,30] reported data on malunions. Our meta-analysis indicates circular external fixator compared to ORIF results in a significantly higher chance of developing malunion (OR, 2.56; 95%CI, 1.12-5.84; I 2 = 49%; p = 0.03) ( Fig 6A).…”
Section: Plos Onementioning
confidence: 99%
“…Their findings indicated that circular external fixator compared to ORIF resulted in a significantly higher chance of developing malunion (OR, 2.56; 95% CI, 1.12-5.84; I2 = 49%; p = 0.03). Whether this is attributable to the treatment itself, the thin-wire circular device, or the severity of the injury was unclear, a prolonged healing time for tibial fractures treated with external fixators has been reported in the literature, which may lead to an increased risk of loss of wire pre-tension, potentially affecting the process of fracture healing [22,23]. It has been shown that changes in the mechanical properties of a fracture site affect the time taken for a fracture to heal, thus modifying the type and proportion of tissues formed [24].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of tibial intercondylar crest fracture in adults is increasing with the increase in sports injuries and traffic accidents. These fractures can recover well in both children and adults if treated effectively at an early stage of tibial eminence avulsion injury [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%